PVDF-TiO2-nZVI Nanocomposite Membranes for the Remediation of Heavy Metal Contaminated Wastewater - Murtala, Namakka; Md. Rezaur, Rahman; Khairul Anwar, Mohamad Said; Bavya Devi, Karuppasamy; Aliyu Abubakar, Shehu (Springer Nature, 2026)
Heavy metal pollution poses a significant threat to environmental and human health. Despite recent advancements in nanofiltration technologies, further innovations are essential to optimize both the heavy metal removal efficiency and hydraulic performance of the nanocomposite membranes. Herein, A TiO2-nZVI nanocomposite was synthesized by impregnating titania (TiO2) with nano zero valent iron (nZVI) via chemical reduction method and subsequently integrated into polyvinylidene fluoride (PVDF) membranes via phase inversion technique. Five distinct membrane configurations were fabricated by varying the nanocomposite loadings. The physicochemical properties of the nanocomposite performance of these membranes were evaluated via various characterization techniques including FESEM, FTIR, EDX, XRD, XPS, TGA, water contact angle, solvent content analysis, pure water flux and Pb2+ removal. The optimal PVDF-TiO2-nZVI membrane was determined via detailed performance evaluation at 10ppm Pb2+ concentration. Influence of concentration on optimum membrane performance was investigated by varying Pb2+ concentrations. The removal efficiencies of the PVDF- TiO2- nZVI membranes were found consistent (>80% across all membranes) with optimum membrane (A4) achieving 91% Pb2+ removal with a sustained hydraulic property during the filtration operation.